2016
DOI: 10.1038/srep36067
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community dynamics in the rhizosphere of a cadmium hyper-accumulator

Abstract: Phytoextraction is influenced by the indigenous soil microbial communities during the remediation of heavy metal contaminated soils. Soil microbial communities can affect plant growth, metal availability and the performance of phytoextraction-assisting inocula. Understanding the basic ecology of indigenous soil communities associated with the phytoextraction process, including the interplay between selective pressures upon the communities, is an important step towards phytoextraction optimization. This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 60 publications
1
36
0
1
Order By: Relevance
“…Controls involved dilute ethanol replacing melatonin (see below) and/or sterile Milli-Q water replacing cadmium. These concentrations were selected to be within the range of those reported to induce effects on soil microbial activities in previous studies for cadmium (Cáliz et al, 2013, Wood et al, 2016) and salt (Rath et al, 2016). Based upon preliminary studies, soils were treated to 80-90% field capacity, to ensure all soils were sufficiently exposed to stressor and melatonin.…”
Section: Methodsmentioning
confidence: 99%
“…Controls involved dilute ethanol replacing melatonin (see below) and/or sterile Milli-Q water replacing cadmium. These concentrations were selected to be within the range of those reported to induce effects on soil microbial activities in previous studies for cadmium (Cáliz et al, 2013, Wood et al, 2016) and salt (Rath et al, 2016). Based upon preliminary studies, soils were treated to 80-90% field capacity, to ensure all soils were sufficiently exposed to stressor and melatonin.…”
Section: Methodsmentioning
confidence: 99%
“…The rhizosphere habitat is affected by spatial and temporal variations in soil properties and the physiological state of the plant (12). Heavy metals in soils could alter the structure of soil microbial communities (13). Previous studies found that presence of heavy metals, including Cd, in soils decreased the microbial biomass and resulted in a shift in the microbial community structure (14)(15)(16).…”
mentioning
confidence: 99%
“…Previous studies found that presence of heavy metals, including Cd, in soils decreased the microbial biomass and resulted in a shift in the microbial community structure (14)(15)(16). On the other hand, heavy metals in soils could increase the prevalence of specific heavy metal-resistant bacteria (13). Although a considerable amount of metalresistant bacteria from the rhizosphere of hyperaccumulators have been isolated using traditional culture-dependent techniques, the microbial assemblages associated with hyperaccumulation remain poorly understood (5,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, soil physical 63 and chemical properties can also be strong drivers of rhizosphere and rhizoplane microbial 64 community composition, particularly on large scales or across soils that vary widely in 65 composition. For example, pH (Bartram et al 2014;Wu et al 2017), salinity (Sardinha et al 2003; 66 Dillon et al 2013), drought (Barnard, Osborne and Firestone 2013; Chodak et al 2015), and the 67 presence of heavy metals (Wood et al 2016) all influence soil and root-associated microbial 68 community structure. Still, the relative importance of plant identity and soil chemistry across soil 69 gradients remains difficult to predict in large part because plant species are often restricted to 70 particular soil types.…”
Section: Introduction 40mentioning
confidence: 99%